Company Profile Development for CV. GP Mandiri Using the Waterfall Method - Reynaldy Alfida Yanur; Trihastuti Yuniati (Politeknik Piksi Ganesha Indonesia, 2024)
A company profile website serves as an effective medium for information and promotion. This study aims to develop a company profile website for CV GP Mandiri using the Waterfall software development method. This method was chosen for its systematic and structured approach, facilitating each stage of development. The website is built using WordPress with the Elementor plugin, allowing for a responsive and user-friendly design. The development process includes stages of requirement analysis, design, implementation, and testing. After implementation, black box testing was conducted to ensure all website functions operate correctly. The testing results indicate that all implemented features, such as the homepage, about the company, services, and contact pages, function as expected. This website not only enhances CV GP Mandiri's visibility in the online world but also provides easy access to information for potential clients. This research is expected to serve as a reference for other companies seeking to develop a website as part of their marketing and communication strategies.